Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.1 - Integer Exponents and Scientific Notation - 4.1 Exercises: 57

Answer

$-\frac{3}{4}$

Work Step by Step

According to the negative exponent rule, $a^{-n}=\frac{1}{a^{n}}$. Therefore, $-2^{-1}-4^{-1}=-(2^{-1}+4^{-1})=-(\frac{1}{2}+\frac{1}{4})=-(\frac{1\times2}{2\times2}+\frac{1}{4})=-(\frac{2+1}{4})=-(\frac{3}{4})=-\frac{3}{4}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.